Schooling in rural societies. - Nash, Roy. (London : New York : Routledge, 2012)
In industrialized societies the needs of people living in remote and sparsely populated areas are easily overlooked, whilst in developing countries the needs of the rural population are at once so obvious and so enormous that our practical concern is blunted. In this volume it is clearly demonstrated that the relationship between environment and schooling is no less pertinent in rural areas than urban areas, although most recent attention has been directed towards the latter. Roy Nash seeks to redress the balance and in this wide-ranging and comprehensive analysis he examines the educational needs of rural people both in the declining periphery of urban Europe and in the resource-starved areas of the developing world.
Includes bibliographical references and index.
Keywords: Education, Rural; Education -- Developing countries